The Role of Family Relationships in Mental Health Distress for Transgender and Gender Nonconforming College Students at University Counseling Centers. Issue 3 (3rd July 2022) - Platt, Lisa F.; Scheitle, Christopher P.; McCown, Claire M.
ABSTRACT: Using data from the Center for Collegiate Mental Health (CCMH), the present study examines the role family relationships have in explaining mental health outcomes for transgender and gender nonconforming (TG/GNC) college students who present to university counseling centers. A structural equation model indicates that TG and GNC collegiate clients report significantly worse family relationships relative to cisgender clients, which contributes to their greater mental distress. Net of their poor family relationships, TG students actually report less mental distress relative to cisgender students. The indirect effect of the TG students' adverse family relationships on mental distress, however, overwhelms this direct effect. Similarly, the analysis shows the gap between cisgender and GNC students in mental distress would be much smaller if it were not for the latter's negative family relationships. These findings improve the understanding of how family relationships impact mental health outcomes for gender minority college students well into early adulthood.